Altered linkage pattern of N-glycan sialic acids in pseudomyxoma peritonei. (17th August 2020) - Nummela, Pirjo; Heiskanen, Annamari; Kytölä, Soili; Haglund, Caj; Lepistö, Anna; Satomaa, Tero; Ristimäki, Ari
Abstract: Pseudomyxoma peritonei (PMP) is a highly mucinous adenocarcinoma growing in the peritoneal cavity and most commonly originating from the appendix. Glycans play an important role in carcinogenesis, and glycosylation is altered in malignant diseases, including PMP. We have previously demonstrated that fucosylation of N-glycans is increased in PMP, but we did not observe modulation of overall sialylation. As sialic acids can be attached to the rest of the glycan via α2, 3- or α2, 6-linkage, we have now analyzed the linkage patterns of sialic acids in tissue specimens of normal appendices, low-grade appendiceal mucinous neoplasms (LAMN), low-grade (LG) PMP and high-grade (HG) PMP. For the linkage analysis, the enzymatically released acidic N-glycans were first treated with ethyl esterification or α2, 3-sialidase digestion followed by MALDI-TOF mass spectrometry. Significant increase in the relative abundance of α2, 6-sialylated and decrease in α2, 3-sialylated N-glycans was observed in PMP tumors as compared to the normal appendices ( P < 0.025). More specifically, increased α2, 6-sialylation ( P < 0.05) and decreased α2, 3-sialylation ( P < 0.01) were detected in afucosylated and monofucosylated N-glycans of PMPs, whereas the less abundant multifucosylated glycans, containing terminal fucose, demonstrated increased α2, 3-sialylation ( P < 0.01). Importantly, the increase in α2, 6-sialylation was also detected between PMP and the appendiceal precursor lesion LAMN ( P < 0.01). The identified glycosylation alterations produce ligands for sialic acid-binding immunoglobulin-like lectins (Siglecs) and sialofucosylated glycans binding selectins, which play a role in the peritoneal dissemination and progression of the disease.